Participation in Context: Neighborhood Diversity and Organizational Involvement in Boston. (September 2013) - Tran, Van C.; Graif, Corina; Jones, Alison D.; Small, Mario L.; Winship, Christopher
We use unique data from the Boston Non–Profit Organizations Study, an innovative survey containing rich information on organizational participation across seven social domains in two Boston neighborhoods, to examine the relationship between ethnic diversity and participation in local organizations. In particular, we identify neighborhood–based social ties as a key mechanism mediating the initial negative association between diversity and participation. In contrast to previous work, we measure participation using both the domain–based and group–based approach, with the former approach uncovering a wider range of organizational connections that are often missed in the latter approach. We also investigate the relationship between interpersonal ties and organizational ties, documenting how primary involvement with an organization facilitates the development of further interpersonal ties and secondary forms of organizational involvement. We then discuss implications of our findings for urban poverty research. Participación en Contexto: Diversidad Barrial e Involucramiento Organizacional en Boston (Van C. Tran, Corina Graif, Alison D. Jones, Mario L. Small y Christopher Winship) Resumen: Usamos información única del Estudio sobre Organizaciones Sin Fines de Lucro en Boston, una encuesta innovadora que contiene información rica sobre participación en organizaciones en siete dominios sociales en dos barrios de Boston, para examinar la relación entre diversidad étnica y participación en organizaciones locales. En particular, identificamos lazos sociales a nivel barrio como un mecanismo clave que media en la asociación negativa entre diversidad y participación. En contraste con trabajos previos, medimos participación usando la aproximación a nivel dominio y a nivel grupo, siendo la primera aproximación la que descubre un gran rango de conexiones organizacionales que muchas veces son desapercibidas por la segunda aproximación. También investigamos la relación entre lazos interpersonales y lazos organizacionales, y mostramos cómo un involucramiento primordial con una organización facilita el desarrollo de vínculos interpersonales posteriores y formas secundarias de involucramiento organizacional. Luego discutimos las implicancias de nuestros resultados para la investigación sobre pobreza urbana.